Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The function $f(x) = 1-f(x-1)$, for positive interger, $x$. If $f(2) = 12$, compute $ f(2012)$

share|cite|improve this question
up vote 7 down vote accepted

$f(x)=1-f(x-1)=1-(1-f(x-2))=f(x-2)=...=f(2)$ is $x$ is even

So, $f(2012)=f(2)=12$

If x is odd, $f(x)$ will reduce to $f(1)=1-f(2)=1-12=-11$

share|cite|improve this answer
So, the answer to f(2) and f(2012) are both 12? And any even number is also 12? – Ctrl Sep 9 '12 at 17:48
Yes, to me that is the case. – lab bhattacharjee Sep 10 '12 at 4:59

Since $x$ is an integer, I will replace it with $k$. Also, instead of $f (x)$ I will use $x_k$. Hence, the rephrased problem is the following:

Problem: for nonnegative $k$ we have that $x_{k+1} = 1 - x_k$. If $x_2 = 12$, compute $x_{2012}$.

Consider the discrete-time dynamical system

$$x_{k+1} = a x_k + b$$

where $a, b \in \mathbb{R}$. It is easy to show that for all $k \geq 0$ we have that

$$x_k = a^k x_0 + \displaystyle\sum_{i=0}^{k-1} a^i b = a^k x_0 + \displaystyle \left(\frac{1 - a^k}{1 - a}\right) b$$

Let's make $a = -1$ and $b = 1$. We then have that the general solution of $x_{k+1} = 1- x_k$ is

$$x_k = (-1)^k x_0 + \displaystyle \left(\frac{1 - (-1)^k}{2}\right)$$

If $x_2 = 12$, then $x_0 = 12$ as well. Note that $x_{2012} = (-1)^{2012} x_0 = x_0 = 12$. I do concede that this approach is total overkill, but next time you see something of the form $x_{k+1} = a x_k + b$, you know what to do.

share|cite|improve this answer
Nice one! ${}{}$ – Pedro Tamaroff Sep 8 '12 at 17:33

Hint $\ $ Iterating a function $\rm\:g\:$ of period $\rm\,n\:$ produces a sequence of period $\rm\,n$

$$\rm g^n = Id,\,\ f(k\!+\!1) = g\,f(k)\ \Rightarrow\ f(k\!+\!n) = g^n f(k) = f(k)\ \Rightarrow\ f(k\!+\!jn) = f(k) $$

Yours is the special case $\rm\:n=2,\:$ since $\rm\:f(k\!+\!1) = 1-f(k) = g\,f(k),\:$ for $\rm\:g(x) = 1\!-\!x,\:$ where $\rm\:g^2(x) = g(g(x)) = g(1\!-\!x) = 1\!-\!(1\!-\!x) = x,\ $ so $\rm\:g^2(x) = x,\:$ i.e. $\rm\ g^2 = Id.$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.